IDH2 R172 Mutations Across Poorly Differentiated Sinonasal Tract Malignancies: Forty Molecularly Homogenous and Histologically Variable Cases With Favorable Outcome. (15th September 2021) - Glöss, Stefanie; Jurmeister, Philipp; Thieme, Anne; Schmid, Simone; Cai, Wei Y.; Serrette, Rene N.; Perner, Sven; Ribbat-Idel, Julika; Pagenstecher, Axel; Bläker, Hendrik; Keber, Ursula; Stadelmann, Christine; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : IDH2 R172 mutations occur in sinonasal undifferentiated carcinoma (SNUC), large-cell neuroendocrine carcinoma (LCNEC), sinonasal adenocarcinomas, and olfactory neuroblastoma (ONB). We performed a clinical, pathologic, and genetic/epigenetic analysis of a large IDH2 -mutated sinonasal tumor cohort to explore their distinct features. A total 165 sinonasal/skull base tumors included 40 IDH2 mutants studied by light microscopy, immunohistochemistry, and genome-wide DNA methylation, and 125 IDH2 wild-type tumors used for comparison. Methylation profiles were analyzed by unsupervised hierarchical clustering, t-distributed stochastic neighbor embedding dimensionality reduction and assessed for copy number alterations (CNA). Thirty-nine histologically assessable cases included 25 (64.1%) SNUC, 8 (20.5%) LCNEC, 2 (5.1%) poorly differentiated adenocarcinomas, 1 (2.7%) ONB, and 3 (7.7%) IDH2 -mutated tumors with ONB features. All cases were high-grade showing necrosis (82.4%), prominent nucleoli (88.9%), and median 21 mitoses/10 HPFs. AE1/AE3 and/or CAM 5.2 were positive in all and insulinoma-associated protein 1 (INSM1) in 80% cases. All IDH2 mutants formed one distinct group by t-distributed stochastic neighbor embedding dimensionality reduction separating from all IDH2 wild-type tumors. There was no correlation between methylation clusters and histopathologic diagnoses. Recurrent CNA included 1q gain (79.3%), 17p loss (75.9%), and 17q gain (58.6%). No CNA differences were observed between SNUC and LCNEC. IDH2 mutants showed better disease-specific survival than SMARCB1-deficient ( P =0.027) and IDH2 wild-type carcinomas overall ( P =0.042). IDH2 -mutated sinonasal tumors are remarkably homogeneous at the molecular level and distinct from IDH2 wild-type sinonasal malignancies. Biology of IDH2 -mutated sinonasal tumors might be primarily defined by their unique molecular fingerprint rather than by their respective histopathologic diagnoses.